Phospholipids of Azotobacter vinelandii - Jurtshuk, Peter (1969)
Analyses of resting cells of Azotobacter vinelandii revealed that numerous phospholipids were present that did not concentrate in the membranous R(3) fraction which carried out electron transport function.